Experience of Laparoscopic Gynecological Surgeries at Kathmandu Model Hospital - Bajracharya, Nishma; Dangal, Ganesh G.; Karki, A.; Pradhan, H.; Shrestha, R.; Bhattachan, K.; Poudel, R. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Laparoscopy has become the most common procedure in recent set-ups. It is now a major diagnostic as well as therapeutic modality for infertility, endometriosis, extrauterine pregnancy and benign ovarian tumors. The aim of the study was to share the experience of gynecological laparoscopic surgeries performed at Kathmandu Model Hospital. Methods: A descriptive study was carried out at Kathmandu Model Hospital from 1st January 2011 to 1st May 2017. All the patients who underwent gynecological laparoscopic surgeries were analyzed for the indication, type of procedure and its complications. Results: Out of 217, majority 24.4 %(n=53) patients were in age group 26-30 years. There were 51.1% (111) cases of ovarian cyst, 12.44%(27) cases of ectopic pregnancy. Eight cases were done with surgeons for cholecystectomy and ovarian cystectomy or hysterectomy. There were 15% (n=32) cases of diagnostic laparoscopy. Total laparoscopic hysterectomy was done in 16% (n=33) cases. Conversion to laparotomy was done in 3%(8) cases. There was one case of vascular injury. Most common immediate post-operative complaint was variable degree of pain, managed with parenteral and oral analgesics. Oral diet started at 4-6th hour post-operatively, and mobilization started after 24 hours. 75% (164) cases had a hospital stay of 2 days and 25%(53) cases stayed for 3 days. Conclusions: Laparoscopic surgery at our hospital has been well demonstrated in terms of reducing postoperative pain and decreasing postoperative morbidity, short hospital stay, and less postoperative recovery time. However, adequate advanced training and devices are needed to perform skillful laparoscopic surgeries.